Knoevenagel Condensation of Aldehydes with Ethyl Cyanoacetate in Water Catalyzed by P4VP/Al2O3-SiO2 - Majid Kolahdoozan; Roozbeh Javad Kalbasi; Zohreh S. Shahzeidi; Farzad Zamani (Journal of Chemistry)
This paper reports the preparation and characterization of poly(4-vinylpyridine) (P4VP) supported on Al2O3-SiO2 and its application for Knoevenagel condensation reaction of various aldehydes with ethyl cyanoacetate in water as a green solvent. The results illustrate that the sample containing 0.6 molar ratio of Al to Si exhibits the highest yield (98%) in the reaction of benzaldehyde with ethyl cyanoacetate with 100% selectivity to the arylidene derivative.